2004
DOI: 10.1536/jhj.45.183
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 and Cardiovascular Diseases

Abstract: SUMMARYInflammatory cytokines are important for both cardiovascular scientists and practicing clinicians. Interleukin-6 (IL-6) has been emphasized by reports of elevated circulating as well as intracardiac IL-6 levels in patients with congestive heart failure (CHF). IL-6 may contribute to the progression of myocardial damage and dysfunction in chronic heart failure syndrome resulting from different causes. As the cause of CHF in cardiomyopathy, myocarditis, allograft rejection, and left ventricular assist devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
180
0
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(188 citation statements)
references
References 55 publications
3
180
0
5
Order By: Relevance
“…In our study, occlusion of the coronary artery was associated with increased serum levels of TNF-a and Il-6 ( Fig. 4A and 4B), indicating that the pro-inflammatory cytokine expression pathway was upregulated, as reported in previous studies [9,13,14]. Treatment with GXEH (15 g/kg) significantly reduced serum levels of TNF-a and Il-6 ( Fig.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In our study, occlusion of the coronary artery was associated with increased serum levels of TNF-a and Il-6 ( Fig. 4A and 4B), indicating that the pro-inflammatory cytokine expression pathway was upregulated, as reported in previous studies [9,13,14]. Treatment with GXEH (15 g/kg) significantly reduced serum levels of TNF-a and Il-6 ( Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Higher levels of pro-inflammatory mediators, including Il-6 and TNF-a, are risk markers for coronary artery disease, and might be related to increased morbidity and mortality in cardiac disease [26]. Il-6 is a key inflammatory factor, and has been implicated in the pathogenesis and progression of CVD [13]. In particular, increased expression of Il-6 in cardiac tissue is associated with myocardial ischemia [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since IL-6 is a potent stimulus for CRP expression in liver, the increased vascular production of IL-6 may represent a positive feedback mechanism for the continued production of CRP from the liver. 17) Several recent studies have indicated that CRP and proinflammatory cytokines such as IL-6 were elevated in OSAS as well as obesity. [13][14][15]18,19) Thus, obesity and OSAS are inflammatory states, as evidenced by elevated levels of serum markers of systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated circulating levels of IL6 have been demonstrated in HF patients, and their serum level expression in cardiac tissue has been correlated with severity of left ventricular function and progression of HF 27 . IL6 has a negative inotropic effect as a consequence of an IL6-induced myocardium hypocontractile state, which explains why patients with uncompensated HF have higher IL6 levels than patients in the recovery phase 28 , reflecting the hemodynamic deterioration in HF patients 29 .…”
Section: Discussionmentioning
confidence: 99%